Implicit conformal design for gradient architected materials - Qianfeng Cao; Ning Dai; Siyuan Yang; Hongqing Dai (Materials & Design)
This paper develops a conformal architected materials design method based on implicit modeling, which enables functional gradient modulation. This method utilizes the mapping relationship between conformal hexahedral element and the cubic bounding box of architected material to construct the signed distance field. To enhance strength and stiffness of the structure, this study integrates the relative density distribution obtained from topology optimization to regulate the density of conformal architected materials through density mapping. Compared to traditional methods, the proposed method not only reduces the damage of the boundary structure caused by cutting, achieving a mutual match between the architected materials and curved geometry, but also retains the ability to control the distribution of relative density. The numerical analysis and experimental results demonstrate that conformal gradient architected materials exhibit better structural strength and stiffness compared to array-generated gradient architected materials, which indicates that the proposed method has potential applications in lightweight design.